2007
DOI: 10.5194/bg-4-377-2007
|View full text |Cite
|
Sign up to set email alerts
|

Minor changes in soil organic carbon and charcoal concentrations detected in a temperate deciduous forest a year after an experimental slash-and-burn

Abstract: Abstract. Anthropogenic fires affected the temperate deciduous forests of Central Europe over millennia. Biomass burning releases carbon to the atmosphere and produces charcoal, which potentially contributes to the stable soil carbon pools and is an important archive of environmental history. The fate of charcoal in soils of temperate deciduous forests, i.e. the processes of charcoal incorporation and transportation and the effects on soil organic matter are still not clear. We investigated the effects of slas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 48 publications
(46 reference statements)
1
35
0
1
Order By: Relevance
“…In fires of high severity the temperatures increase soil redness, especially at temperatures of 300-500 • C (Terefe et al, 2008) or > 600 • C ( Ketterings and Bigham, 2000;Ulery and Graham, 1993), which is attributed to the destruction of the organic matter and increase in iron oxides such as hematite (Terefe et al, 2005). In contrast, low-severity fires darken the soil as a result of the incorporation of ash/charcoal into the soil surface and matrix (Eckmeier et al, 2007). These authors observed that soil lightness of colour had a significant negative correlation with charcoal carbon.…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…In fires of high severity the temperatures increase soil redness, especially at temperatures of 300-500 • C (Terefe et al, 2008) or > 600 • C ( Ketterings and Bigham, 2000;Ulery and Graham, 1993), which is attributed to the destruction of the organic matter and increase in iron oxides such as hematite (Terefe et al, 2005). In contrast, low-severity fires darken the soil as a result of the incorporation of ash/charcoal into the soil surface and matrix (Eckmeier et al, 2007). These authors observed that soil lightness of colour had a significant negative correlation with charcoal carbon.…”
Section: Introductionmentioning
confidence: 53%
“…With time, despite the significant differences of soil Munsell colour value between plots, the soil became lighter in the burned plot. This may be attributed to the incorporation of burned residues into the first top centimetres of the soil, reducing soil surface darkness (Eckmeier et al 2007;Pereira et al, 2012b, c;Woods and Balfour, 2011). The black ash cover has implications in the soil environment in the immediate period after the fire (e.g.…”
Section: Soil Munsell Colour Valuementioning
confidence: 99%
See 2 more Smart Citations
“…After burning events, either wildfires or deliberate burning, a fraction of the charred organic material left on the soil surface is incorporated into the soil mineral matrix (Eckmeier et al, 2007). The lipid distribution patterns in some soils in Spain that were affected by vegetation burning were dominated by short-chain even carbon numbered n-alkanes (Tinoco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%